Management of Radius Non-Union with In-Situ Square Nail and Fresh Ulna Fracture with Positive Ulnar Variance: Dual Bone Plating and the Novel Use of an Ulna Strut Graft for Radius Non-Union and Simultaneous Ulnar Variance Correction—A Case Report - Kumar, Surinder; khanna, Rutul; singh, Rishavjit; Bansal, Janam (Journal of Neonatal Surgery, 2025)
Introduction: Radius non-union in the presence of prior hardware, along with a fresh ulna fracture and positive ulnar variance, presents a complex challenge. Correcting ulnar variance is essential for addressing wrist pain and restoring normal forearm biomechanics. Case Report: We present the case of a 60-year-old female who sustained a right forearm injury following a slip. She had a square nail inserted into the radius 15 years ago, which contributed to non-union. The recent trauma resulted in a fresh fracture of the ulna shaft and positive ulnar variance, contributing to wrist pain. The surgical intervention involved the removal of the square nail, ulna shortening, and plate fixation of both the ulna and radius. The radius non-union was treated by freshening the bone edges, and an ulnar strut graft harvested from the shortened ulna was used to prevent radius shortening, stabilize the non-union and to simultaneously correctthe positive ulnar variance. Conclusion: This case illustrates a comprehensive approach to managing radius non-union with prior hardware, combining radius and ulna plating with ulna shortening and using the same ulnar strut graft to prevent further radius shortening, to correct the ulnar variance and to helprestore stability to the forearm.